KEDUDUKAN WALI HAKIM MENURUT UNDANG-UNDANG PERKAWINAN DAN PENERAPANNYA DI KOTA PALU - Suhri Hanafi; Ilmiati Ilmiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
The guardian in marriage that must be met for the bride, but if there is no guardian nasab or may not bring it or do not know where he lives or magical or adlal or are reluctant to marry her then that act is the Guardian Judge. On the other hand, the position and authority of the guardian judge was not clearly mentioned in the Marriage Law, as well as the Implementation Regulations. The results showed that Law No. 1 of 1974, though as the Marriage Act but not one clearly chapter provisions governing the transfer of guardianship nasab trustee to trustee hands judges. For applicability in practice Religious Affairs issued Ministerial Decree No. 30 of 2005 on the Guardian Judge, referring to the Islamic law, the Islamic Law Compilation tend to Shafi and legislation in force. In certain circumstances by legislation, including the law guardian authorizes judges to act as a guardian of marriage as a substitute and not as representatives of a guardian nasab therefore; 1) nasab guardian is entitled to nothing at all, or in carrying out an unobstructed view of the ceremony consent, such as not qualified to be the guardian of marriage, occult, and so forth; 2) Guardian adhol. But the new judge guardian can act as a guardian of marriage when there is a decision PA / guardian stating Judge it really adhol